EDUKASI MANAJEMEN KONFLIK KEUANGAN DALAM RUMAH TANGGA DAN KONFLIK LINGKUNGAN KERJA BAGI WANITA KARIR - Maya Richmayati; Elminaliya Sandra; Nur Isra Laili; Sarmini; Ade Sarmini (PUAN INDONESIA, 2023)
Women have potential that needs to be expended. Now many women work with variegated motives. It is not uncommon for working women to cause problems in themselves, their internal families, and their work environment. Many advantages are obtained if women work in addition to earning income, extensive relationships, and increased knowledge and skills. Women in the household serve as wives as well as mothers, of course, there will be problems if women have activities outside, this is where communication and delegation of tasks are important. The role of women in the family is also as a family accountant, who controls the planning and budget in her family so that her family's balance sheet can be maintained. Conflicts in the work environment are inevitable, caused by various factors, namely an uncomfortable organizational climate, toxic friends, high workload, and competition from fellow workmates. The purpose of this service activity is to provide knowledge and motivation so that women understand their role and also have strategies for unraveling problems whenever did happen. The method used is to expose directly to the participants according to the phenomena that occur. The result of this service activity is that the participants are enthusiastic in asking questions and understanding how the strategy should be done, because with a good strategy the goal of what is to be achieved can be achieved